Analisis Perjanjian Jaminan Fidusia terhadap Parate Eksekusi dan Perlindungan Hukumnya bagi Kreditur (Studi Kasus Pada BMT dan BPR Syariah Di Ponorogo) - Martha Eri Safira (Justicia Islamica, 2014)
Based on Law No. 42 of 1999 concerning Fiduciary Guarantees (abbreviated as UUJF), in addition to the credit agreement as the parent agreement, there should also be a fiduciary guarantee binding agreement to facilitate BMT and BPR Syariah in processing fiduciary guarantee certificates. The privilege of a fiduciary security certificate is that the BMT and BPR Syariah have the authority to execute and auction the fiduciary collateral themselves without having to go through the judicial process in court. However, because a fiduciary security certificate has never been issued, in the credit process at BMT and BPR Syariah, what is often a problem is the difficulties often faced by the BMT, namely if the debtor defaults or breaks promises in fulfilling his obligations, difficulty executing and auctioning the fiduciary collateral. And in the event of execution and auction, based on the UUJF, the implementation of execution and auction carried out by BMT and BPR Syariah in Ponorogo Regency so far has actually violated the law or can be considered illegal, even though BMT and BPR Syariah have dept collectors as officers who execute collateral objects.